Results of a cardiac screening program in elite football players in new zealand - Davis, A. J.; Gray, B.; Driscoll, T.; Orchard, J. W.; Hamilton, B.; Doughty, R. N.; Fulcher, M.; Orchard, J. J. (Science and Medicine in Football, 2025)
Cardiac screening of elite footballers for conditions associated with sudden cardiac arrest/death (SCA/D) is a requirement of Fédération Internationale de Football Association (FIFA). This study aimed to report the findings, cardiac diagnoses, and outcomes from the New Zealand Football (NZF) screening program for FIFA tournaments since 2012. Footballers were screened with a personal/family history, physical examination, resting 12-lead electrocardiogram (ECG) and transthoracic echocardiogram. An audit (March 2024) reviewed screening records, comprising ECGs, echocardiograms, demographic data, follow-up testing, and diagnoses. A footballer was included if their screening episode included an ECG trace and an echocardiogram (with a report in English) and if there were sufficient details about the screening outcome. Rare results were reported as <5 to protect anonymity. If a footballer had multiple screenings, only the first was included. One hundred and forty-seven footballers (60% female, mean age 19.2 ± 3.7 years) were included. There were <5 diagnoses of conditions associated with SCA/D. No footballer retired for cardiac reasons and there were no incidents of SCA/D during the audit period. 4.8% of ECGs were abnormal; however, no patient was subsequently identified to have underlying structural heart disease on echocardiography. In screening echocardiograms, females had significantly lower indexed left ventricular end-systolic and diastolic volumes compared to males. The ECG and echocardiographic findings in this screening cohort were similar to those of other football populations.